Flotation separation of molybdenite from chalcopyrite using rhodanine-3-acetic acid as a novel and effective depressant - Wang, Changtao; Liu, Runqing; Wu, Meirong; Xu, Zhijie; Tian, Mengjie; Yin, Zhigang; Sun, Wei; Zhang, Chenyang (Minerals engineering, 2021)
[Display omitted] •Flotation separation CuFeS2 and MoS2 was achieved using 3-Rd as depressant.•Rhodanine-3-acetic acid (3-Rd) selective adsorbed on chalcopyrite surface.•3-Rd chemisorbed on CuFeS2 through COO and CSS- group.•Fe sites on CuFeS2 surface was more adsorption active than Cu sites. The selective separation of molybdenite from chalcopyrite is difficult because of their similar floatability in the presence of a collector. In this study, rhodanine-3-acetic acid (3-Rd) was first applied in molybdenite flotation as a novel chalcopyrite depressant, and its depression effect and mechanism were systematically investigated by flotation tests, density functional theory (DFT) calculation, zeta potential measurements, and X-ray photoelectron spectroscopy (XPS) analysis. Single mineral flotation results indicated that 3-Rd can selectively depress chalcopyrite flotation, whereas its effect on molybdenite is negligible. Mixed mineral and bench flotation tests further proved that 3-Rd is an efficient chalcopyrite depressant. The first-principle periodic calculations based on DFT predicted that 3-Rd prefers to adsorb onto Fe rather than Cu because of the more negative adsorption energy of the COO or CSS group on Fe in the chalcopyrite surface. Zeta potential measurements demonstrated that 3-Rd is adsorbed on chalcopyrite surface more selectively, and its adsorption strength is higher than that on molybdenite surface. XPS analysis further confirmed that 3-Rd is chemisorbed on chalcopyrite surface by binding with Fe active site and is adsorbed on molybdenite surface through hydrogen bonding and electrostatic interactions.